Understanding self‐injury recovery: Views from individuals with lived experience. Issue 12 (23rd July 2019) - Lewis, Stephen P.; Kenny, Therese E.; Whitfield, Kristen; Gomez, Jennifer
Abstract: Objective: Nonsuicidal self‐injury (NSSI) recovery has typically been conceptualized through the lens of formal frameworks or as the cessation of NSSI. These understandings, however, have been developed largely devoid of views from those with lived NSSI experience, who may offer novel and critical insights. To advance the conception of NSSI recovery, the current study elicited such views. Methods: Two hundred and thirty‐three emerging adults with a history of NSSI (77% female, mean age = 18.9 years), responded to open‐ended questions regarding recovery. Results were thematically analyzed using an inductive approach. Results: Responses yielded seven themes: (a) recovery is complete NSSI cessation; (b) recovery is more than cessation; (c) recovery involves lingering NSSI features; (d) recovery involves developing resilience; (e) recovery is a process; (f) evolution in understanding recovery; and (g) recovery is a subjective experience. Conclusion: Recovery seems to be multifarious, nonlinear, and subjective. Conceptual and clinical implications are discussed.